KEBIJAKAN PENEMPATAN TENAGA KERJA LOKAL PADA SEKTOR MIGAS DI KABUPATEN BENGKALIS TAHUN 2019 - Deva Yomi Erlangga; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this research is to find out the policies for placing lokal workers in the oil and gas sector in Bengkalis Regency in 2019. The theory used in this research is 1. Content of Policy includes the following interest affected, type of benefits, extent of change envision, site of decision making, program implementer, resources committed. 2. Context of Policy includes the following power, interest and strategy of actor involved, institution and regisme characteristic, compliance and responsivenes. Data collection techniques used in this study were observation, interviews, and documentation. This research was conducted at the Bengkalis District Manpower and Transmigration Office. The results of the study show that the policy for placing local workers in Bengkalis Regency has not beend maximized. This can be seen from the local workers placed in oil and gas sector companies that have not reached 50% as mandated by Bengkalis Regency Regional Regulation number 04 of 2004. Supervision carried out by the Bengkalis Regency Manpower and Transmigration Office for oil and gas sector companies has also not been maximized due to a shortage of human resources, as well as the absence of strict sanctions given by the Bengkalis Regency Manpower and Transmigrasi Service.